Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Given:
[tex]H(x)=\frac{4}{x^2+4}[/tex]• First Let's go through the, mean value theorem.
If a function f is continuous on the closed interval [a, b] and is differenciable on the open interval (a, b), the there is a number c in (a, b) such that;
[tex]f^{\prime}(c)=\frac{f(b)-f(a)}{b-a}[/tex]The function given satisfies all this conditions.
a=-3 and b= 3
• Let's ,differentiate, the function given using quotient rule to get f'(c).
[tex]H^{\prime}(c)=\frac{(x^2+4).0-4(2c)}{(c^2+4)^2}[/tex][tex]=\frac{-8c}{(c^2+4)^2}[/tex]• Next, is to find H(3)
Substitute x=3 into the function H(x)
[tex]H(3)=\frac{4}{3^2+4}=\frac{4}{9+4}=\frac{4}{13}[/tex]• Similarly find H(-3)
[tex]H(-3)=\frac{4}{(-3)^2+4}=\frac{4}{9+4}=\frac{4}{13}[/tex]Substitute the values we've gotten so far into;
[tex]H^{\prime}(c)=\frac{H(3)-H(-3)}{3-(-3)}[/tex][tex]\frac{-8c}{(c^2+4)^2}=\frac{\frac{4}{13}-\frac{4}{13}}{9}[/tex]• Evaluate
[tex]\frac{-8c}{(c^2+4)^2}=\frac{0}{9}[/tex]From the above;
-8c = 0 ⇒ c =0
(c² + 4)² = 9
Take the root of both-side
c² + 4 = 3
c² = 3 - 4
c² = -1
c=±√-1
c = ± i
But from the definition c is in [-3, 3]
Hence, c = 0
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.